P02.01 Altered FoxM1 expression contributes to the meningioma malignancy and can be a critical target for the tumor progression. (19th September 2018) - Kang, S H; Kim, H; Park, K; Ryu, B; Yu, M; Choi, Y; Park, S
Abstract: Background: Meningioma, the most common primary brain tumor, is intractable for various treatment modalities in case of malignant progression. The transcription factor Forkhead box M1 (FoxM1) is overexpressed in malignant meningioma. However, the functional importance of this factor in human meningioma is not known. In this study, we examined FoxM1 expression and oncogenic potential in meningioma. Material and Methods: To verify the correlation between FoxM1 expression and meningioma grades, human meningioma tissues and cell lines were used. In addition, FoxM1 associated target gene profiles, malignant phenotype, in vivo tumorigenesis and chemotherapeutic drug sensitivity analysis were performed under altered regulation of FoxM1. Results: It revealed that FoxM1 expression is positively correlated with meningioma grade, including recurrent tissues derived from primary tumors by mRNA assay and immunostain. Inhibition of FoxM1 suppresses cell proliferation, anchorage-independent growth in vitro, and tumorigeneicity in vivo by regulation of downstream targets including beta-catenin, cyclin D1, p21, MMP9, EMT profiles in malignant meningioma. In siomycin A treatment, a selective FoxM1 inhibitor, IOMM Lee malignant meningioma cells result in more sensitization for growth inhibition than SF4433 benign meningioma. In case of Siomycin A pretreatment, decreased FoxM1 and Ki67 expression are found at tumor tissue in vivo. Conclusion: These data showed that FoxM1 may have a driving role for meningioma progression and its inhibition is effective strategy in meningioma therapy.